2021
DOI: 10.14814/phy2.14757
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen treatment is associated with a decrease in cytokine levels in patients with necrotizing soft‐tissue infection

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 59 publications
(90 reference statements)
0
25
1
Order By: Relevance
“…G‐CSF is a pro‐inflammatory cytokine suggested to be involved in sepsis pathogenesis and to promote important functions on mature myeloid cells and the innate immune system 27,28 . It was recently associated with disease severity and 30‐day mortality in an observational study including 242 NSTI patients, 20 but we observed no apparent effect of IVIG on G‐CSF.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…G‐CSF is a pro‐inflammatory cytokine suggested to be involved in sepsis pathogenesis and to promote important functions on mature myeloid cells and the innate immune system 27,28 . It was recently associated with disease severity and 30‐day mortality in an observational study including 242 NSTI patients, 20 but we observed no apparent effect of IVIG on G‐CSF.…”
Section: Discussioncontrasting
confidence: 62%
“…This was a post hoc analysis of the INSTICT trial; a single‐centre randomised, blinded, placebo‐controlled trial performed from February 2014 to March 2016 at Rigshospitalet, University of Copenhagen 16 . The cytokine measurements were made available for the present post hoc analysis, as these previously have been evaluated in a larger observational setting which partly included the INSTICT trial 20 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 Finally, HBOT has shown to induce substantial effects on the expression of immune modulatory cytokines by decreasing pro-inflammatory cytokines such as IL-1, IL-6, and TNF-alfa and elevating the anti-inflammatory cytokine IL-10. 24 It is interesting to report other effects that HBOT is able to exert on wounds as it encourages collagen production by fibroblast, which leads to the growth of granulation tissue, an essential step in wound healing. 25 Moreover, the increase in oxygen tension, which persists for several hours after therapy, is responsible for angiogenic properties of HBOT.…”
Section: Discussionmentioning
confidence: 99%